salsabilaanm Pengaruh Self Image Congruence Terhadap Keputusan Pembelian Dimediasi Oleh Brand Trust Pada Maskapai Penerbangan Air Asia - Salsabila Nadhifah; Reminta Lumban Batu (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Indonesian aviation industry, especially domestic airlines, is booming and overgrowing with the emergence of many airlines since Law No. 15 of 1992 was enacted. This study aimed to see the effect of self-image congruence on purchasing decisions mediated by a brand trust on AirAsia Airlines. This research was conducted using descriptive and verification methods. The sampling technique of this research is non-probability sampling using the Hair formula. The types of data used in this study are primary and secondary data. The data were processed using path analysis. This study proves that self-image congruence has a positive and significant effect on purchasing decisions through brand trust in Air Asia Airlines. This research implies that self-image congruence can indirectly influence purchasing decisions through brand trusts, which is seen from the actual indicator of self-image or how consumers see their true selves. Brand character indicators can make the brand have an essential role in determining consumer decision making to trust a brand, and this is because consumers make judgments before buying it.